An improved evaluation method for the undrained shear strength of uniform soft clay in the nonfull flow state based on ball penetration simulations. (November 2022) - Gu, Zhongde; Guo, Xingsen; Nian, Tingkai; Fu, Cuiwei; Zhao, Wei
Abstract: A ball penetrometer provides an efficient method for accurately assessing the undrained shear strength of soft marine clays. However, evaluating the undrained shear strength in the nonfull flow state remains in the exploratory period. In this paper, ball penetrations in soft clays in the nonfull flow state are simulated using a coupled Eulerian‒Lagrangian approach, and the mechanism of soft clays from the open cavity state to the trapped cavity state is investigated in depth. Furthermore, the net penetration resistance in the nonfull flow state is achieved by in situ stress correction coefficients based on the contact area between the ball probe and surrounding clay, and the bearing capacity factors are then resolved. On this basis, an improved method for evaluating the undrained shear strength is proposed, combined with the net penetration resistance and the bearing capacity factors. Finally, the improved method is preliminarily validated by penetration tests in two types of soft clays of a special ball that can measure the earth pressure at different positions on the probe and ultimately validated by comparisons with the results of other studies, which indicates that the improved method provides good accuracy to assess the undrained shear strength of soft clays.